Aerobic power and field test results of amateur 15-a-side rugby union players - Sant'anna, R. T.; de Souza Castro, F. A. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: The aim of the present study was to verify whether it is possible to predict aerobic power in amateur 15-a-side rugby union players through the Yo-Yo Intermittent Recovery Test Level 1 (Yo-Yo IRT1) and the 5-meter Multiple Shuttle Test (5-m MST).